Eksistensi Ilmu dalam Perspektif Filsafat, Kebudayaan, dan Agama di Era Global dan Digital - Nabila Rezky Palenza; Yeni Karneli; Puji Gusri Handayani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This article discusses the existence of science from the perspective of philosophy, culture, and religion in the global and digital era. Through an interdisciplinary approach, this article examines how the integration of science, cultural values, and religious principles can strengthen human civilization amidst the challenges of globalization and digitalization. In the process, this study highlights the importance of philosophical foundations in the development of science, the contribution of culture in providing local context to the application of science, and the role of religion in providing a moral and ethical framework. The results of the study show that collaboration between these three aspects can create a civilized, tolerant, and adaptive society to changes in the times. Thus, this integration becomes an important foundation for the development of sustainable and meaningful human civilization in the modern era.